This food crisis is different: COVID-19 and the fragility of the neoliberal food security order. Issue 7 (9th November 2020) - Clapp, Jennifer; Moseley, William G.
ABSTRACT: Our analysis situates the current COVID-19 induced food crisis within a longer-term historical perspective on policy responses to past food crises. We argue that the legacies left by these past policies created vulnerabilities in the face of the present crisis, which is characterized by three interlocking dynamics: disruptions to global food supply chains, the loss of income and livelihoods due to the global economic recession, and uneven food price trends unleashed by a set of complex factors. We make the case that the COVID-19 pandemic marks an inflection point and demands a different set of policy responses that work toward fundamentally transforming food systems.